Evaluating Awareness and Practices of Dental Students on Disinfection Methods for Extracted Infectious human Teeth at Prince Sultan Military College of Health Sciences - Alhanouf mohammed alahmadi,; Rawan Talal Sairafi,; Alaa Faihan Al Harithi,; Samah ali alfuraydi,; Abeer Abdullah Al-Awfi,; Noura Ahmed Aldosari,; Yosra Zubedi kabi,; Wadha Ayed Alkhibery,; Shahad Mazen Hamoh,; Mashael Mazyad Almutairi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Undergraduate and postgraduate dental students refine mechanical and clinical patient treatment abilities utilizing excised human teeth. They must adhere to preclinical and clinical safety guidelines, as educational methodologies reflect clinical proficiency. In order to evaluate the comprehension of infective disinfection techniques for excised human teeth among undergraduate and bridge dental students at Prince Sultan Military College of Health Sciences. Given that Saudi Arabia has not conducted comprehensive research in this region, it necessitates evaluation.Thus, this research encompassed female undergraduate and bridging dental students at PSMCHS in Dhahran, KSA. Data was obtained by a self-administered questionnaire and results showed that 61.5% of female dental students at PSMCHS are knowledgeable about managing extracted teeth, whereas 8.2% are uncertain. Other observations among the study showed that Employment history and educational background did not influence depression rates. Substantial link between the quantity of Depression rates differ by academic level, with senior nursing students exhibiting the highest frequency at 25.94%. This study revealed that dental students recognize the importance of cleaning or sterilizing extracted teeth prior to handling them and acknowledge that human teeth are infectious.Additional variables, such as the source of transmission and the disposal of extracted teeth, revealed a deficiency of practical information regarding human excised teeth.